"A metamorphosis of the educator": A hermeneutic phenomenology study of the perceptions and lived experiences of the 6–12 educator in transitioning from teacher‐centered to student‐centered learning. Issue 2 (9th January 2021) - McPherson, Peter J.
Abstract: Background: Despite large amounts of research documenting, the transition to student‐centered learning from the perspective of the student, minimal literature exists describing the lived experience, and perceptions of Idaho teachers and principals when transitioning from teacher‐centered to student‐centered learning. Aim: The purpose of this study was to explore in specific detail the perceptions and lived experiences of Idaho teachers and building principals in transitioning to student‐centered learning, and thereby assists in filling in the literature gaps surrounding this topic. Six middle and high school teachers and four building principals were asked to describe and reflect on their perceptions and lived experiences in transitioning from teacher‐centered to student‐centered learning. Methods: This hermeneutical, qualitative phenomenological study used a constructivist theoretical framework to assist the researcher in identifying and conveying each participant's deep, rich experience. In‐depth interviews were used to gather responses, and the data were transcribed and coded into three major themes, with keywords and terms from the participants supporting each theme. Results and Discussion: The three themes that emerged when identifying and describing the perceptions and lived experiences of the participants in transitioning to student‐centered learning were a shift in philosophy of education, changes in methods and pedagogy, and the importance of relationships between teachers, principals, and students. Conclusion: Key findings from the study suggest that in order to effectively transition from teacher‐centered to student‐centered education, cognitive changes in an educator's philosophy and mindset, along with social adjustments addressing relationships, connections, and experiences must be recognized and even embraced.